Globalizacija in religije - Smrke, Marjan (Teorija in praksa, 2014)
Discussed herein are five aspects of relations between globalisation and religion: (1) the processes of religious globalisation, (2) the effects of globalisation on religions and religiosity, (3) the effects that religion has on globalisation, (4) relations between old and new transnational religions in a global world, and (5) interactions between globalisation and religion locally, i.e. within the Slovene environment. Divergent and often contradictory processes were detected. The theory of existential security appears promising in explaining the divergent effects of religious globalisation worldwide, whilst it also enjoys some application in the interpretation of religious change locally.
Keywords: Globalizacija; Globalization; Religija; Religion; Secularization; Sekularizacija